Culture, Memory, and Narrative Self-Making. (December 2017) - Wang, Qi; Song, Qingfang; Kim Koh, Jessie Bee
Narrative entails an active act of sense making through which individuals discern meaning from their experiences in line with their cultural expectations. In this article, we outline a theoretical model to demonstrate that narrative can be simultaneously used to examine cognitive processes underlying remembering on the one hand and to study the process of meaning-making that holds implications for self and well-being on the other. We argue that these two approaches, oftentimes overlapping and inseparable, provide critical means to understand the central role of culture in shaping memory and self-identity. We further demonstrate that the integration of culture in narrative research can, in turn, greatly enrich our understanding of the cognitive and social underpinnings of narrative.